Ray tracing em tempo real usando hierarchical scene signed distance fields - Menezes, Vitor Peixoto (2019)
Ray tracing is an important technique for obtaining photo-realistic images. The basic algorithm is well known and consists of tracing rays from a synthetic camera position by calculating the color of objects colliding with the rays. The number of rays varies, but it is usually proportional to pixel amount, which raises the complexity of ray tracing technique because it deals with a large number of collisions between rays and objects. Therefore, acceleration methods are required. Recently, proposed solutions changed the way that an object is represented. These solutions use the signed distance field (SDF) to represent an object. Thus, using a hierarchical signed distance fields approach, our work presents a new manner of representing a static scene that is capable of decreasing the image generation time. The algorithm introduces a pre-processing scheme that subdivides the scene and stores it on disk for later use. Initially, each object must be transformed to a signed distance field representation and after that, the hierarchy of the scene must be created and saved to disk. During rendering, the previously generated structure is loaded from disk and used to calculate the ray tracing.